Efektivitas Penggunaan Media Komik Digital (Cartoon Story Maker) dalam pembelajaran Tema Selalu Berhemat Energ - Riwanto, Mawan Akhir; Wulandari, Mey Prihandani (PANCAR, 2018)
The purpose of this study is to know the effectiveness of using digital comic media to improve student learning achievement. The proposed study was carried out through a quasi experiment with the design of one group pretest-posttest. The subjects in this study were fourth grade students of SD Negeri 3 Linggasari Kembaran UPK, Kembaran District, Banyumas Regency. Digital comic media used in science learning using Cartoon Story Maker software on themes selalu berhemat energi. The results of this study show that the use of digital comics made with Cartoon Story Maker software can increase the effectiveness of learning in theme selalu berhemat energi. The results of data calculations indicate that Sig Paired Samples Statistics 0,000 and a correlation value of 0.766. While the results of the Sig 2-tailed Paired Samples Test = 0,000. This shows that the use of digital comic media has a significant influence on the learning process